Ultimate strength and axial strain of FRP strengthened circular concrete columns. Issue 1 (1st January 2018) - Ahmed, Shamil K.
Abstract: In this paper, a comprehensive study of CFRP and GFRP strengthened circular concrete columns is presented. Previous experimetal work is reviewed including the effect of different parameters affecting the strenght and behaviour of circular concrete columns confined with FRP and new equations are propsed which has more accurate prediction of the enhanced circular concrete column strength and behvaviour than previously proposed ones.